The Role of Creativity and Project Management in Enhancing Service Quality of Advertising Agencies: A Qualitative Approach. Issue 1 (February 2018) - Levin, Elizabeth; Thaichon, Park; Quach, Sara; Lobo, Antonio
This research study aims to investigate the role of creativity and project management as important aspects of service quality. The context is the advertising industry which is highly competitive and its clients have very specific needs and expectations. Data was collected using indepth interviews with marketing managers and project leaders who were responsible for the advertising needs of their organisations. The findings provide detailed insights into the nature of creative competence, project management process and project outcomes from the clients' perspective. Creative competence includes an assessment of the creative work produced by the advertising agencies and their staff. The project management processes reflect the need for detailed plans and budgets to be developed and communicated, as well as having a clear process for change management once the project scope and plan have been signed off. This study is the first of its kind using a qualitative approach to investigate the role of creativity and project management in enhancing the service quality of advertising agencies.